2004
DOI: 10.1002/mrc.1411
|View full text |Cite
|
Sign up to set email alerts
|

Bonding and33S NMR chemical shielding in the thiophosphoryl group

Abstract: B3LYP and MP2 calculations at the 6-311 + G(nd,p) level (with n = 2 for second-row elements and n = 1 otherwise) were carried out using the atoms-in-molecules (AIM) approach to characterize the thiophosphoryl bond. A series of R(3)PS molecules were studied and compared with the corresponding R(3)PO systems. As with the phosphoryl bond, one cannot distinguish the thiophosphoryl bond from a standard P=S double bond by comparing bond distances. On the basis of the P=S bond in HP=S having a reference bond order of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…[9][10][11][12][13][14] In early work, Nguyen et al 9,10 showed that singlet HPS was the most stable isomer, lying some 16.2 kcal/mol below triplet HSP. The derived ground state HPS structure was in good agreement with the more recent experimental structure derived from microwave data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] In early work, Nguyen et al 9,10 showed that singlet HPS was the most stable isomer, lying some 16.2 kcal/mol below triplet HSP. The derived ground state HPS structure was in good agreement with the more recent experimental structure derived from microwave data.…”
Section: Introductionmentioning
confidence: 99%
“…8 The HPS vibrational frequencies were predicted to be ν 1 (PH stretch) = 2195 cm −1 , ν 2 (bend) = 877 cm −1 , and ν 3 (PS stretch) = 647 cm −1 . Other studies examined the electronic stabilization of the PS group by various substituents, 11 the bonding in the thiophosphoryl group, 12 the dynamics of the isomerization, and H 2 elimination reactions of H 3 PS to form HPS, 13 and the reactions that could form PS, including HPS as an intermediate. 14 The most recent and highest level theoretical calculations were those done in connection with the microwave study, 8 in which coupled cluster [CCSD(T)] theory was used to calculate the equilibrium structure, harmonic, and anharmonic force fields, quartic centrifugal distortion constants, nuclear quadrupole coupling constants for DPS, and phosphorus nuclear spin-rotation constants.…”
Section: Introductionmentioning
confidence: 99%
“…5 Chesnut and co-workers used a different analysis, also based on AIM, but used delocalization indices and a par-ticular description of bond order based on the Cioslowski-Mixon bond localization scheme. 10 By this method, the ionic contribution to the total bond P-S (or P-O) bond order for Me 3 PdS (or dO) is 36% or 43%, respectively. They state that the ionicity of the P-O bond is about 67%, whereas that of the P-S bond is about 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Several computational studies suggest that the best description of such bonds is a polar sigma bond, supplemented by additional electrostatic bonding as evidenced by distorted lone pairs on the oxo atom or a single strongly polarized bond, depending, again, on the computational model used and the exact type of compound being studied. [2][3][4][5][6][7][8][9][10][11] Of practical interest is the corresponding bond strength because of the utility of such compounds as oxygen or sulfur sinks in atom-transfer reactions. The extraordinary P-O bond dissociation energy of 130 kcal/mol for Ph 3 PO 12 has led to its very common use in such chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of back-bonding contributes to the DI, providing a stronger character than a single bond and its concomitant shortening of the bond distance. A similar scheme has been applied to sulfuryl, thiophosphoryl, and bicyclic sulfoxide derivatives …”
Section: 5 Delocalization Indicesmentioning
confidence: 99%